Cockroaches as potential mechanical vectors for mites infestation the first report in Kuantan - Mat Yusof, Afzan (Academic Journals Inc., USA, 2018)
Background: Cockroaches have been long hated by people due to their creepiness and considered as pests. Since mites share the same environment as cockroaches, there are a number of possibilities for mites to be found on the cockroaches. Objectives: Hence, the study aimed to identify the occurrence of mites carried by cockroaches from two food stalls and two restaurants in Indera Mahkota, Kuantan, Pahang, Malaysia. Materials and Methods: A total of 179 cockroaches from the species of Periplaneta americana were caught and processed for identification of mites. The mites were observed under light microscope. Results: Microscopic evidence showed that 102 cockroaches carried mites. The percentage of mites’ occurrence was higher in the food stalls as compared to the restaurants. Conclusions: Overall, the study found that cockroaches potentially serve as mechanical vectors for mites. By reducing the cockroach infestation in food premises, the risk of transmission of dangerous mites via cockroaches also can be reduced.